Automated vision-based system for parallel contactless micromanipulation - Vela, Emir (2013)
This paper presents the automated parallel noncontact manipulation of glass beads ranging from 30 up to 300 μm in size under water. Non-contact micromanipulation is performed by generating controllable laser-induced thermocapillary flows that are capable of dragging the beads. Automated manipulation process is achieved with visual servoing in order to accurately manipulate the beads in a parallel and high-speed manner. Image correlation allowed to detect the bead positions and to provide these positions to a mirror scanner that addressed the IR laser beam at a certain position from the bead. By scanning the laser beam from one bead to another, automated parallel manipulation of beads at speeds in the range of mm·s-1 was demonstrated.